Penetrating Scleral Injury with Intraocular Foreign Body. A Case Report - Anay Martínez Díaz; Armando Rafael Milanés Armengol; Katia Molina Castellanos; Eduardo Hernández Peña (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Ocular trauma is a health problem in the world today and a common cause of visual impairment leading to severe sequelae and psychological disorders. The case of a 46-year-old male patient who attended the Ophthalmology emergency services of the Dr. Gustavo Aldereguía Lima University General Hospital of Cienfuegos, recounting that while hammering iron on iron he felt that something entered his right eye, is presented. He suffered from pain, tearing, red eye and blurred vision. A penetrating scleral injury with an intraocular foreign body was diagnosed. Its study was conducted through biomicroscopy, orbital x-ray and ocular ultrasound. Surgical treatment by extracapsular lens extraction with intraocular lens implantation was performed using Blumenthal technique and pars plana approach for removal of the intraocular foreign body.